Ankylosing spondylitis and psoriatic arthritis: clinical and economic consequences of the use of etanercept - Sacchi, Viola; Zaniolo, Orietta; Olivieri, Ignazio (Farmeconomia. Health economics and therapeutic pathways, 2010)
Spondyloarthritis (SpA) is the name for a family of inflammatory rheumatic disease that can affect the spine and joints, ligaments and tendons. Spondyloarthritis disease include ankylosing spondylitis, reactive arthritis, psoriatic arthritis, the spondylitis associated with the inflammatory bowel diseases and the undifferentiated spondyloarthritis. The most common treatments prescribed for spondyloarthritis are nonsteroidal anti-inflammatory drugs (NSAIDs) given in combination with disease-modifying antirheumatic drugs (DMARDs). Due to a recently suggested role of the tumour necrosis factor (TNFa) in the pathogenesis of SpA, new therapies specifically blocking TNFa have been investigated. Anti-TNF medications currently available on the Italian market are etanercept, infliximab and adalimumab. The aim of the present work was to furnish a clinical and pharmaco-economical profile of etanercept in treatment of psoriatic arthritis and ankylosing spondylitis based on a review of the published literature. Economical evaluations performed in several countries indicate that total treatment costs are lower with etanercept and adalimumab as compared to infliximab, mainly because of differences in the route of administration. Etanercept appears to be cost effective for the treatment of psoriatic arthritis and ankylosing spondylitis especially considering improved health related quality of life and lower medical costs due to superior efficacy of treatment.